1968
DOI: 10.1126/science.162.3856.918
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Inhaled Plutonium Oxide- 239 Pu Particles by Pulmonary Macrophages

Abstract: Pulmonary macrophages and plutonium particles were removed by washing the lungs of rats that had inhaled plutonium oxide-(239)Pu. A significant amount of plutonium was found in multiple washings of the same lung. The removal of toxic particles by washing is of potential therapeutic value. Particles were phagocytized by macrophages during the first 3 hours and retained within these cells for up to 25 days. Nearly all particles in washings were found in macrophages after the second day. The percent of macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

1969
1969
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…Data indicate a positive correlation between the amount of particles cleared and the number of these phagocytic cells in the lung (18). A number of inhalable substances such as carbon (1,6,18,32), diesel exhaust (33), PbO (34), NiC12, NiO (35-37), CdCl2 (38), CO (39), Pb2O3 (8,40), cigarette smoke (24,(41)(42)(43), cotton dust (44), quartz (45) and other environmental substances (46,47) can promote the influx of macrophages into the pulmonary racemus. Little is known about the mechanisms of action that stimulate this migration or about the fate of these immigrant cells.…”
Section: Alterations In Numbersmentioning
confidence: 99%
“…Data indicate a positive correlation between the amount of particles cleared and the number of these phagocytic cells in the lung (18). A number of inhalable substances such as carbon (1,6,18,32), diesel exhaust (33), PbO (34), NiC12, NiO (35-37), CdCl2 (38), CO (39), Pb2O3 (8,40), cigarette smoke (24,(41)(42)(43), cotton dust (44), quartz (45) and other environmental substances (46,47) can promote the influx of macrophages into the pulmonary racemus. Little is known about the mechanisms of action that stimulate this migration or about the fate of these immigrant cells.…”
Section: Alterations In Numbersmentioning
confidence: 99%
“…The removal of 239Pu02 particles by lavage from excised rat lungs was demonstrated in 1968 (Sa68) and reported again in 1969 (Sa69a; Sa69b). The first use of lavage to remove radioactive particles from lungs of living animals was reported in 1969 (Pf69a).…”
Section: Introductionmentioning
confidence: 87%
“…After the injection of tritiated amino acid into a specific neuronal site, the isotope is incorporated into protein within the neuronal cell body (2)(3)(4)(5). This protein then moves along the axons that originate from the neurons in the injected region, finally appearing in their terminal portions.…”
mentioning
confidence: 99%
“…After vitreal injection of tritiated leucine, the label rapidly appears in retinal proteins (2,4,5). Scintillation counting (12) of the monkey visual system after injection with tritiated leucine indicated that subsequently some of this incorporated label moved along the optic nerve.…”
mentioning
confidence: 99%